Hubungan Jumlah dan Kepadatan Penghuni Rumah serta Keberadaan Nyamuk dengan Frekuensi Menggigit Nyamuk Aedes aegypti Saat Mencari Darah di Kabupaten Cirebon Provinsi Jawa Barat - Lukman Hakim; Asep Jajang Kusnandar (ASPIRATOR - Journal of Vector-borne Disease Studies, 2010)
Dengue hemorrhagic fever (DHF) is an infectious disease caused by dengue virus with the widest spread in the Asian region. In Indonesia, every year is always an outbreak in some provinces, the largest occurred in 1998 and 2004 with the number of patient mortality by 79 480 people with 800 people. To know the risk factor for dengue transmission in Cirebon District that had a high DHF cases, had been conducted the research with calculating the number and density of humans at the houses and also survey of density of Aedes aegypti pre-adult and adult stages.The research was resulting that the house index (HI) of Ae. aegypti is 58%, while homes found Ae. aegypti adults is 46%, 6 of which house is the house that is not found larvae / pupae of mosquitoes. The laboratory tests found that the frequency of biting Ae. aegypti mosquitoes average 4.5 times per day, at least 2 times and no more than 7 times per day. Number of people bitten by adult mosquitoes average of 3.1 people per day, is at least 2 people and maximum 5 people per day. Based on the statistically test, it is known that there is significant correlation between the number of inhabitants of the house and the presence of mosquito larvae / pupa of Ae. aegypti mosquito with biting frequency, whereas the most dominant variable was the presence of larvae / pupae of mosquitoes. Furthermore, it is advisable to do the cleaning intensification of Aedes breeding places inand outside the home including those hidden. It is also necessary to place residential settings so that the number of occupants per house so less.